Favourite Cupcakes and Cheescakes - Carroll, Anthony (Australia R & R Publication Marketing, 2008)
"In this book we offer a broad range of tasty delights, designed for ease of preparation, to give the satisfaction that a cupcake or cheesecake brings. These recipes are valuable assets to any kitchen library: Clear step-by-step instructions with realistic preparation times; A simple nutritional breakdown with every recipe; Serving suggestions to turn dishes into complete meals; No special kitchen equipment needed; All recipes tried and tested."--Back cover.
Include Color Illustrations, Glossary and Index
Keywords: Baking Cakes -- Cupcakes